Algorithmic Game Theory Third International Symposium, SAGT 2010, Athens, Greece, October 18-20, 2010. Proceedings - Kontogiannis, Spyros; Koutsoupias, Elias; Spirakis, Paul G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the Third International Symposium on Algorithmic Game Theory, SAGT 2010, held in Athens, Greece, in October 2010. The 28 revised full papers presented together with 2 invited lectures were carefully reviewed and selected from 61 submissions. The papers are intended to cover all important areas such as solution concepts, game classes, computation of equilibria and market equilibria, convergence and learning in games, complexity classes in game theory, algorithmic aspects of fixed-point theorems, mechanisms, incentives and coalitions, cost-sharing algorithms, computational problems in economics, finance, decision theory and pricing, computational social choice, auction algorithms, price of anarchy and its relatives, representations of games and their complexity, network formation on the internet, congestion, routing and network design and formation games, game-theoretic approaches to networking problems, and computational social choice.
When the Players Are Not Expectation Maximizers -- How Do You Like Your Equilibrium Selection Problems? Hard, or Very Hard? -- A Simplex-Like Algorithm for Fisher Markets -- Nash Equilibria in Fisher Market -- Partition Equilibrium Always Exists in Resource Selection Games -- Mixing Time and Stationary Expected Social Welfare of Logit Dynamics -- Pareto Efficiency and Approximate Pareto Efficiency in Routing and Load Balancing Games -- On Nash-Equilibria of Approximation-Stable Games -- Improved Lower Bounds on the Price of Stability of Undirected Network Design Games -- On the Rate of Convergence of Fictitious Play -- On Learning Algorithms for Nash Equilibria -- On the Structure of Weakly Acyclic Games -- A Direct Reduction from k-Player to 2-Player Approximate Nash Equilibrium -- Responsive Lotteries -- On the Existence of Optimal Taxes for Network Congestion Games with Heterogeneous Users -- Computing Stable Outcomes in Hedonic Games -- A Perfect Price Discrimination Market Model with Production, and a (Rational) Convex Program for It -- The Computational Complexity of Trembling Hand Perfection and Other Equilibrium Refinements -- Complexity of Safe Strategic Voting -- Bottleneck Congestion Games with Logarithmic Price of Anarchy -- Single-Parameter Combinatorial Auctions with Partially Public Valuations -- On the Efficiency of Markets with Two-Sided Proportional Allocation Mechanisms -- Braess$1 (Bs Paradox for Flows over Time -- The Price of Anarchy in Network Creation Games Is (Mostly) Constant -- Truthful Fair Division -- No Regret Learning in Oligopolies: Cournot vs. Bertrand -- On the Complexity of Pareto-optimal Nash and Strong Equilibria -- 2-Player Nash and Nonsymmetric Bargaining Games: Algorithms and Structural Properties -- On the Inefficiency of Equilibria in Linear Bottleneck Congestion Games -- Minimal Subsidies in Expense Sharing Games.s
Keywords: Computer science; Electronic data processing; Computer simulation; Computer Science; Simulation and Modeling; e-Commerce/e-business.; Models and Principles; Computers and Society; Numeric Computing; Probability and Statistics in Computer Science